WHAT IS THE MAJOR FACTOR ON THE KIDNEY INJURY INDUCED BY HYPERTENSION OR HYPERHOMOCYSTEINEMIA. (April 2021) - Xu, Rui; Gao, Ning
Abstract : Objective: As we all know kidney injury could be induced by hypertension or hyperhomocysteinemia (HHcy). What is the major factor? HHcy plays a synergistic role with hypertension in vascular injury; however, the relationship between HHcy and hypertension in renal injury remains unclear. Here, we sought to evaluate the relationship between HHcy and hypertension in the context of renal injury and to elucidate the mechanism of action underlying this relationship. Design and method: Wistar Kyoto (WKY) and spontaneously hypertensive (SHR) rats were randomized into WKY, WKY+HHcy, SHR, and SHR+HHcy groups. Blood pressure, plasma homocysteine, creatinine, serum malondialdehyde (MDA), serum superoxide dismutase (SOD), and urinary albumin creatinine ratio (UACR) were measured. mRNA and protein expression levels of NOX2, NOX4, and nephrin in the kidneys were also examined. Results: The WKY+HHcy group exhibited lower serum SOD levels, relative to the WKY group, along with higher levels of both serum MDA and UACR. Similar effects were observed in the SHR+HHcy group, relative to the SHR group. Moreover, compared with the levels in the WKY+HHcy group, mean SOD levels in the SHR+HHcy group were lower, while mean MDA and UACR levels were higher. Higher mRNA and protein expression levels of NOX2 and NOX4, along with lower mRNA and protein expression levels of nephrin, were observed in the kidneys of WKY+HHcy and SHR+HHcy rats, relative to SHR and WKY controls, respectively. Furthermore, the mRNA and protein levels of NOX2 and NOX4 were higher and the mRNA and protein levels of nephrin were lower in the SHR+HHcy group than in the WKY+HHcy group. In addition, compared with WKY+HHcy group, the UACR level of SHR group was higher. Conclusions: HHcy appears to synergistically increase hypertensive renal damage by enhancing oxidative stress. However, hypertension remains a major risk factor for renal impairment compared to HHcy.